2018
DOI: 10.3390/f9070392
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Impacts of Forest Recovery on Water Yield in Two Large Watersheds in the Cold Region of Northeast China

Abstract: In northern China, large-scale reforestations were implemented to restore the ecosystem functions (e.g., hydrology function). However, few studies have been conducted to quantify the relative contributions of forest recovery to water yield in boreal forest region across the globe. In this study, the impacts of forest recovery on the changes in mean annual water yield were assessed in two large forested watersheds in the boreal forest region of northeast China using three different approaches. As commonly consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Forest water consumption increased gradually due to the increased biomass under the current forest management policies and rapid climate warming. If precipitation does not increase or become stable in the future, the reduction of annual water yield due to global warming forest regrowth is likely to cause stress of water demand for irrigation and wetlands in downstream [32,73]. In addition, our result indicated that the watersheds covered by primitive larch forests had a lower high flows and flood risk as compared with deciduous conifer broad-leaved mixed forests.…”
Section: Implications and Uncertaintymentioning
confidence: 74%
“…Forest water consumption increased gradually due to the increased biomass under the current forest management policies and rapid climate warming. If precipitation does not increase or become stable in the future, the reduction of annual water yield due to global warming forest regrowth is likely to cause stress of water demand for irrigation and wetlands in downstream [32,73]. In addition, our result indicated that the watersheds covered by primitive larch forests had a lower high flows and flood risk as compared with deciduous conifer broad-leaved mixed forests.…”
Section: Implications and Uncertaintymentioning
confidence: 74%
“…Of the 15 papers we deemed appropriate for this review, one of the studies took place in Argentina, ten took place in China, two in Ethiopia, one in Wales, and one in the USA (Table 1) [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The large-scale restorations occurred in a variety of habitat types.…”
Section: Resultsmentioning
confidence: 99%
“…It can also be the case, however, that some ecosystem services decline in value. Three of the studies highlighted in this review from China showed that ecosystem variables reflecting water yield decreased since restoration efforts (Table 1, [40,41,43]). Water yield at the local scale may not benefit from landscape-scale restoration; however, increased evapotranspiration from restoration at these local scales will favor the cross-continental transport of moisture vapor and thus, increased precipitation in locations distant from the ocean-based hydrological cycle [95].…”
Section: How Landscape-scale Restoration Can Be Used To Improve Ecosymentioning
confidence: 96%
“…The accumulated snowmelt air temperature refers to the sum of the temperature over 0 °C during the snowmelt period. We acknowledge that there may be some spatial heterogeneity in precipitation across both watersheds but we believe this heterogeneity to be minimal because the study region is mainly characterized by low hills with gentle undulations [29]. In order to test such inference, the…”
Section: Datamentioning
confidence: 99%
“…The accumulated snowmelt air temperature refers to the sum of the temperature over 0 • C during the snowmelt period. We acknowledge that there may be some spatial heterogeneity in precipitation across both watersheds but we believe this heterogeneity to be minimal because the study region is mainly characterized by low hills with gentle undulations [29]. In order to test such inference, the annual gridded precipitation data in both watersheds from a separate database, "0.5 • × 0.5 • gridded database of annual surface precipitation in China" [30], have been used to test the accuracy of the precipitation data obtained from both climate stations.…”
Section: Datamentioning
confidence: 99%